A descriptive and comparative grammar of Andalusi Arabic (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2012)
Andalusi Arabic is a close-knit bundle of Neo-Arabic dialects resulting from interference by Ibero-Romance stock and interaction of some Arabic dialects. These dialects are mostly Northern but there are also some Southern and hybrid ones, brought along to the Iberian Peninsula in the eighth century A.D. by an invading army of some thousands of Arab tribesmen who, in the company of a much larger number of partially Arabicized Berbers, all of them fighting men alone, succeeded in establishing Islamic political rule and Arab cultural supremacy for a long while over these lands. The study of Andalusi Arabic is of enormous interest to the Arabic dialectologist, as well as a subject of paramount importance to those concerned with the medieval literatures and cultures of Western Europe.